Evaluation of planting arrangment and methods on quantitative and qualitative characteristics of tomato (Lycopersicon esculentum) seeds - H. Khazaei (علوم و فناوری بذر ایران)
In order to evaluatethe the effects of planting arrangment and methods on quantitative and qualitative characteristics of tomato seed (Lycopersiconesculentum, cv. Karoon), a factorial experiment carried out based on a randomized complete block design with three replications at two locations of Khorasan Razavi province in 2012. Three inter row space including 120, 140 and 160 centimeters, three intra plant space including 30, 40 and 50 centimeters, and also two planting methods including one and two row per ridge were selected as treatments. Traits under consideration were fruit and seed yield, number of fruit per plant, number of seed per fruit, thousand seed weight, hectolitre weight, percentage and rate of germination. Compound analysis of variance for locations showed that increasing in inter row space from 120 to 160 centimeters had a significant increase in number of fruit per plant and number of seed per fruit 11.4 and 9.6 percent, respectively. Decreasing in intra plant space from 50 to 30 centimeters showed a significant decrease in number of fruit per plant, number of seed per fruit, thousand seed weight and hectolitre weight 20.7, 11.1, 4.5 and 3.9 percent, respectively. Two row per ridge had a significant decreasing in number of fruit per plant, number of seed per fruit, thousand seed weight and hectolitre weight 6.3, 7.8, 4.1 and 1.8 percent, respectively. The highest and lowest fruit and seed yield were obtained in Rokh (two row per ridge and 120×30 cm planting pattern) and Toroq (one row per ridge and 140×50 cm planting pattern) regions, respectively with 2.7 and 3.1 times difference. Generally, two row arrangement method and 150×30 centimeters planting pattern have positive effect on seed quantity and quality criteria.